Comparison of dietary sterols on growth, survival and midgut gland histology of prawn Artemesia longinaris (Decapoda, Penaeidea) - Haran, Nora Selma (2013)
Two trials were conducted to evaluate the growth, survival and midgut gland histological conditions of Argentine prawn Artemesia longinaris nourished with diets having different sterols. Juvenile individuals of 0.97-1.01 and 1.75g were fed five semi purified diets containing 2% cholesterol, ergosterol, stigmasterol or β-sitosterol and a control ration without sterols for a period of six weeks. The digestive gland of intermoult prawn were dissected out and processed for light microscope studies. Rations having cholesterol and stigmasterol were found to result in higher growth than the other diets. Also individuals fed these diets showed midgut gland tissues similar to those of wild animals. The histoarchitecture of the midgutgland of A. longinaris fed ergosterol, β-sitosterol and the control diet were found to result in several alterations such as dismissing of cellular high, loss of the star–shaped lumen of the tubules, retraction of basal membranes and absence of brush border, haemocytic infiltration, cells with foamy appearance, cellular necrosis and hypertrophy and finally tissue disorganization. The results obtained suggest that addition of cholesterol or stigmasterol to feeds for this species, promotes an increase in weight and the hepatopancreas shows typical histological structure like wild prawns.